Relationship between muscle strength, physical performance, quality of life and bone mineral density among postmenopausal women at risk of osteoporotic fractures - Chua, Siew Kuan; Singh, Devinder Kaur Ajit; Zubir, Khairunisa; Chua, Yin Yian; Rajaratnam, Bala S; Mokhtar, Sabarul Afian (Science, Engineering and Health Studies, 2020)
Information regarding the relationship between muscle strength, physical performance (PP), quality of life (QoL) and bone mineral density (BMD) in adults with osteoporosis is limited. The aim of this study was to determine the relationship between these four parameters and the determinants of lumbar spine BMD in postmenopausal women at risk of osteoporotic fractures. In this cross-sectional study, 50 participants aged 55 and above were recruited from an orthopaedic clinic. A hand dynamometer, a load cell system and short physical performance battery were used to measure hand grip strength (HGS), back extensor muscle strength (BEMS) and PP, respectively. To assess QoL and BMD, European QoL questionnaire and bone densitometry were used, respectively. WHO fracture calculator (FRAX®) results showed that postmenopausal women in this study were at moderate risk of major osteoporotic fractures (13.28 ± 7.10%) and had a high risk of hip fracture (3.35 ± 2.54%). Stepwise regression analysis demonstrated that greater HGS and body mass index (BMI) were determinants of lumbar BMD, accounting for 28.4% of total variance independent of age. Improved muscle strength and having a higher BMI could preserve lumbar BMD and prevent osteoporotic fractures in postmenopausal women.